The Influence of the Autonomic Nervous System on the Vital Functions of the Body (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The autonomic nervous system regulates basic life processes such as blood pressure and respiratory rate. This system operates automatically (autonomously), that is, its functioning does not depend on human will. Diseases of the autonomic nervous system can affect any part of the body and any process. Autonomic disorders can be both reversible and progressive.The autonomic nervous system is the part of the nervous system that controls internal organs, including blood vessels, stomach, intestines, liver, kidneys, bladder, genitals, lungs, pupils, heart, sweat and salivary glands, and digestive glands.After the autonomic nervous system receives information about the state of the organism and the environment, it stimulates processes in the organism, which can be carried out by the sympathetic division, or slows them down, which can be carried out by the parasympathetic division.